2012
DOI: 10.1111/j.1442-2042.2012.03085.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar functional outcomes after partial nephrectomy for clinical T1b and T1a renal cell carcinoma

Abstract: Abbreviations & AcronymsObjectives: To examine the medium-term functional outcomes of partial nephrectomy for clinical T1b renal cell carcinoma, and to compare them with those of radical nephrectomy for clinical T1b and with those of partial nephrectomy for clinical T1a tumors. Methods: The participants of this study were patients operated for clinical T1a and clinical T1b tumors operated at Tokyo Women's Medical University, Tokyo, Japan, between January 1979 and June 2011. A total of 67 patients underwent par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
3
11
1
Order By: Relevance
“…On the other hand, a prospective study from Van Poppel et al [19] demonstrated inferior 10-year OS rates in PN patients compared to RN patients. In this study, in accordance to the contemporary literature [15][16][17] , we found superior survival rates for PN patients compared to RN patients in the study collective. Based on these reports and our own results, we confirm that PN is oncologically safe even in large RCCs.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, a prospective study from Van Poppel et al [19] demonstrated inferior 10-year OS rates in PN patients compared to RN patients. In this study, in accordance to the contemporary literature [15][16][17] , we found superior survival rates for PN patients compared to RN patients in the study collective. Based on these reports and our own results, we confirm that PN is oncologically safe even in large RCCs.…”
Section: Discussionsupporting
confidence: 91%
“…NSS has been the therapeutic standard in a majority of patients with a T1a renal tumor, and the indication of NSS has recently been extended to selective T1b and T2 disease [3,4,5]. The surgical option for localized renal tumors largely depends on their anatomical features, and a classification or scoring system, which can quantitatively assess the anatomical feature of the tumor with high reproducibility, is thus warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional cohorts generally exhibited minimal difference in overall survival between RN and PN (low strength of evidence). 18,19,21,22,24,27,28,31,32,36,60,[86][87][88] Authors of studies with statistically significant OS advantage for PN acknowledged differences in baseline characteristics (ie selection bias) that may have contributed to the observed findings. 23,25,26,74 In 10 SEER studies comprising the majority of patients in this analysis PN was associated with a statistically significant overall survival benefit compared to RN for clinical stage T1a tumors but not for T1b tumors.…”
mentioning
confidence: 99%